Integration of Analysis Power Flow, Short Circuits, and Coordination Relays on the System Power Distribution: A Systematic Literature Review - Thriskadewi Umi Rasyda; Alisha Gita Gumilang (Universitas Panca Marga, 2026)
This literature review comprehensively examines the integration of power flow analysis, short-circuit analysis, and relay coordination in electrical power distribution systems. Drawing upon 25 peer-reviewed journal articles and textbooks published between 2015 and 2023, this review synthesizes methodologies, findings, and trends across three interrelated domains. Power flow analysis underpins system planning and operational efficiency; short-circuit analysis ensures equipment rating adequacy and safety; and protective relay coordination guarantees selective fault isolation and system continuity. The increasing penetration of distributed generation (DG), photovoltaic (PV) systems, and battery energy storage (BESS) presents unprecedented challenges to traditional protection paradigms, necessitating adaptive and integrated analytical approaches. This review identifies research gaps, highlights emerging tools such as heuristic optimization and smart-grid-enabled adaptive protection, and proposes directions for future integrated distribution system analysis frameworks.